2011
DOI: 10.1007/s10584-011-0116-7
|View full text |Cite
|
Sign up to set email alerts
|

East African food security as influenced by future climate change and land use change at local to regional scales

Abstract: Climate change impacts food production systems, particularly in locations with large, vulnerable populations. Elevated greenhouse gases (GHG), as well as land cover/land use change (LCLUC), can influence regional climate dynamics. Biophysical factors such as topography, soil type, and seasonal rainfall can strongly affect crop yields. We used a regional climate model derived from the Regional Atmospheric Modeling System (RAMS) to compare the effects of projected future GHG and future LCLUC on spatial variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…The higher range of predictions for maize across GCMs, reflects the uncertainty of climate prediction impacts using GCMs. Similar results were obtained by Moore et al (2012) who reported between 20% and 30 % decrease in maize yields towards mid-century in Morogoro. They attributed the uncertainty to combined effects of greenhouse gas emissions and land cover land use change (LCLUC).…”
Section: Uncertainty On Climate Change Impact and Adaptation Optionssupporting
confidence: 89%
See 1 more Smart Citation
“…The higher range of predictions for maize across GCMs, reflects the uncertainty of climate prediction impacts using GCMs. Similar results were obtained by Moore et al (2012) who reported between 20% and 30 % decrease in maize yields towards mid-century in Morogoro. They attributed the uncertainty to combined effects of greenhouse gas emissions and land cover land use change (LCLUC).…”
Section: Uncertainty On Climate Change Impact and Adaptation Optionssupporting
confidence: 89%
“…While results from the current study agree and/or disagree with some large scale studies, their strength emanate from the consideration of local crop specific varieties and management practices and the consideration of relevant weather information. In the central zone, the study showed that the magnitude of maize yield decline at least to mid-century is not likely to exceed 25%, results which are in agreement with Moore et al (2012). In contrast, Mwandosya et al (1998) projected a decline in maize yields of between 80 and 90% towards the end of the century.…”
Section: Model Evaluation and Crop Yield Projectionssupporting
confidence: 69%
“…These increases in temperatures influence the decline in maize yields in the southern southwestern sub-ecological zones of Tanzania. The study by Moore et al (2011) suggested that increase in temperatures reduce the length of growing season that can either decrease yields (if currently warm) or increase yields (if currently cool).…”
Section: Discussionmentioning
confidence: 99%
“…In [24] a regional climate model to compare the effects of projected greenhouse gases concentration and land use land cover change on spatial variation of crop yields in East Africa has been used. In addition, the extent to which projected rainfall and temperature trends are, or are not, yet becoming evident in daily and seasonal weather observations have also been assessed [13,15,14].…”
Section: Access To Literature and A Database Of Projectsmentioning
confidence: 99%